Il ruolo del capitale intellettuale nel successo delle strategie di merger & acquisition delle start-up - Masciarelli, Francesca; Di Pietro, Francesca; Serpente, Greta (Piccola Impresa / Small Business, 2020)
The article proposes a case study of a Merger and Acquisition (M&A) processes in Italy between a temporary agency and an innovative start-up. The aim of the study is to investigate which component of the intellectual capital affects the trust of the companies involved in the M&A process. Results show the key role of trust in start-up’s human capital for the integration of the innovative service into the acquiring company. We suggest that the success of the M&A is given by our model named “circular vision of intellectual capital”.